The efficacy of extracorporeal photopheresis to arrest bronchiolitis obliterans in lung allograft recipients was compared between two automated photopheresis instruments. Issue 12 (12th October 2018) - Chionis, Lisa; Grossman, Brenda J.; Hachem, Ramsey; Commean, Paul; Derfler, Mary Clare; Vedantham, Suresh; Dodds, Kathy; Spitznagel, Edward; Atkinson, Jeff; Despotis, George
Abstract : Background: The most common instruments used for extracorporeal photopheresis (ECP) treatment in the United States are the UVAR XTS and the CELLEX devices (Therakos, West Chester, PA). When compared to the UVAR XTS instrument, the efficacy of the CELLEX instrument to arrest the decline in lung function in patients with chronic lung allograft dysfunction (CLAD) related to bronchiolitis obliterans (BOS) has not been previously evaluated. Methods: The relative efficacy of the CELLEX vs UVAR XTS ECP instruments was assessed by comparing the difference in rates of FEV1 decline before and after ECP treatment and survival in two series of lung allograft recipients with BOS who had been treated with these instruments. Results: Similar Slope Difference values for change in rate of decline (6 months Post ECP ‐ Pre ECP) were observed between the two cohorts (UVAR XTS: 85 ± 109 mL/month vs CELLEX: 76 ± 128 mL/month, p=0.72). A similar percentage of patients responded to ECP (UVAR XTS: 77% vs CELLEX: 89%; p=0.36) i.e., as defined as a positive difference in slope between the rate of decline of FEV1 before and 6 months after ECP. Survival at either 6 (p=0.89) or 12 (p=0.8) months after the start of ECP was not associated with instrument used despite a trend in higher early mortality (34% vs 17%, p=0.054) in the patients who were predominately treated with the CELLEX. Conclusions: Our data support the use of the CELLEX for prospective studies designed to evaluate the merits of ECP in this population.